2010
DOI: 10.1001/archpediatrics.2009.287
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Policies of Pediatric Journals

Abstract: To study whether specific recommendations aiming to improve publication practice were included in author instructions of pediatric journals. Design: We identified 69 journals in the subject category "pediatrics" of the Journal Citation Report 2007 that publish original research articles. From the journals' online author instructions, we extracted information regarding endorsement of the Uniform Requirements for Manuscripts (URM) of the International Committee of Medical Journal Editors and of 5 major reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 44 publications
6
30
0
Order By: Relevance
“…Meerpohl et al (2010) reported that 78 % of pediatric journals required authors to disclose COI. Blum et al (2009) and Mathur et al (2013) discovered that journals with relatively high impact factors had easily accessible policies on disclosing conflict of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Meerpohl et al (2010) reported that 78 % of pediatric journals required authors to disclose COI. Blum et al (2009) and Mathur et al (2013) discovered that journals with relatively high impact factors had easily accessible policies on disclosing conflict of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Meerpohl et al . analyzed the online author instructions of 69 journals indexed in the subject category 'pediatrics’ of JCR 2007 with regard to endorsement of the Uniform Requirements for Manuscripts (URM) of the ICMJE, of five major reporting guidelines, disclosure of conflicts, and trial registration [18]. Only 16 (23%) of the included 69 journals either recommended or required trial registration.…”
Section: Discussionmentioning
confidence: 99%
“…Some journals have only recently required and/or printed COI statements and funding disclosure statements [17,25,26]. We identified current COI and funding disclosure policies for each of the journals in which our study articles appeared.…”
Section: Methodsmentioning
confidence: 99%